CFD Convective Flow Simulation of the Varying Properties of CO2-H2O Mixtures in Geothermal Systems. (23rd March 2015) - Yousefi, S.; Atrens, A. D.; Sauret, E.; Dahari, M.; Hooman, K.
Abstract : Numerical simulation of a geothermal reservoir, modelled as a bottom-heated square box, filled with water-CO2 mixture is presented in this work. Furthermore, results for two limiting cases of a reservoir filled with either pure water or CO2 are presented. Effects of different parameters including CO2 concentration as well as reservoir pressure and temperature on the overall performance of the system are investigated. It has been noted that, with a fixed reservoir pressure and temperature, any increase in CO2 concentration leads to better performance, that is, stronger convection and higher heat transfer rates. With a fixed CO2 concentration, however, the reservoir pressure and temperature can significantly affect the overall heat transfer and flow rate from the reservoir. Details of such variations are documented and discussed in the present paper.